Farm spatial decision support system - Aljack, Elsadig Abdalla; Daud, Mohamed; Mansor, Shattri; Bardaie, Mohd Zohadie (Universiti Putra Malaysia, 1999)
To increase productivity, efficiency and competitiveness of farms, mechanized agricultural operations are needed. Likewise, developing and promoting appropriate new technologies are needed in the decision making and management process. Farm decision-makers are faced with not only the need to manage traditional facilities, but, also, complex environmental management requirements. This paper proposes a farm Spatial Decision Support System conceptual model. The model uses Decision Support System (DSS) and Geographical Information System (GIS) to handle farm spatial and attribute information. The real power of GIS derives from the integration of database and graphics capabilities with engineering design, analytical, and cost models. Thus, through supporting “what-if”, “where is what”, “where is best”, “what effect what”, and “what relationship exit” analyses about operations, the expansion and maintenance of the scheme can be used for decision making.